1997
DOI: 10.1097/00002030-199712000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, efficacy, plasma drug concentrations and protease mutations in patients with advanced HIV infection treated with ritonavir plus saquinavir

Abstract: The response to ritonavir plus saquinavir in advanced HIV infection is unpredictable. A minority of patients respond with disappearance of HIV viraemia. In other patients, rapid cumulative emergence of protease mutations conferring resistance to treatment cannot always be prevented by good compliance and relatively high plasma drug levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
56
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 11 publications
2
56
0
1
Order By: Relevance
“…Low drug levels have been associated with self-reported non-adherence (72;73) and virologic failure (74)(75)(76)(77), but not all studies have shown a benefit to measuring serum drug levels. In one study an abnormally low drug level had a specificity of 88% for detecting adherence of 90% or less (75), but another study found that the addition of drug levels to a composite adherence measure did not improve the composite measure's ability to predict viral load (78).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Low drug levels have been associated with self-reported non-adherence (72;73) and virologic failure (74)(75)(76)(77), but not all studies have shown a benefit to measuring serum drug levels. In one study an abnormally low drug level had a specificity of 88% for detecting adherence of 90% or less (75), but another study found that the addition of drug levels to a composite adherence measure did not improve the composite measure's ability to predict viral load (78).…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Los beneficios de la terapia antiviral pueden verse comprometidos cuando aparecen ciertos factores, como defectos de la inmunidad del huésped, alta capacidad del virus para desarrollar resistencia a los fármacos (13,(17)(18)(19)(20)(21), y pobre cumplimiento del tratamiento. A esto se suma el alto costo y el bajo acceso a los medicamentos en los países en vía de desarrollo, así como la alta toxicidad de los mismos (22,23). La estrategia del manejo actual es el uso de terapia antirretroviral altamente activa (highly active antiretroviral treatment, HAART) (24,25).…”
unclassified
“…While previous studies have shown the cross-sectional association of the virologic response with a higher C trough (1,5,6,9,15), the discrimination of C trough , C max , and AUC as pharmacodynamic predictors for PI activity is generally not feasible due to the correlation between these parameters. This is the first longitudinal study to demonstrate that the C trough is associated with the in vivo antiviral activities of PIs, independent of C max and AUC.…”
Section: Discussionmentioning
confidence: 95%
“…C trough s of PIs have been associated with virologic suppression in several clinical studies (1,5,6,9,15), as have AUCs in other studies (1,14). Enhancement of indinavir C trough s by the addition of ritonavir to the antiretroviral drug regimen could theoretically enhance virologic suppression.…”
mentioning
confidence: 96%
See 1 more Smart Citation